Strain-encoded magnetic resonance: a method for the assessment of myocardial deformation - Korosoglou, Grigorios; Giusca, Sorin; Hofmann, Nina; Patel, Amit R.; Lapinskas, Tomas; Pieske, Burkert; Steen, Henning; Katus, Hugo; Kelle, Sebastian (ESC heart failure, 2019)
This study aims to assess the usefulness of strain-encoded magnetic resonance (SENC) for the quantification of myocardial deformation (‘strain’) in healthy volunteers and for the diagnostic workup of patients with different cardiovascular pathologies. SENC was initially described in the year 2001. Since then, the SENC sequence has undergone several technical developments, aiming at the detection of strain during single-heartbeat acquisitions (fast-SENC). Experimental and clinical studies that used SENC and fast-SENC or compared SENC with conventional cine or tagged magnetic resonance in phantoms, animals, healthy volunteers, or patients were systematically searched for in PubMed. Using ‘strain-encoded magnetic resonance and SENC’ as keywords, three phantom and three animal studies were identified, along with 27 further clinical studies, involving 185 healthy subjects and 904 patients. SENC (i) enabled reproducible assessment of myocardial deformation in vitro, in animals and in healthy volunteers, (ii) showed high reproducibility and substantially lower time spent compared with conventional tagging, (iii) exhibited incremental value to standard cine imaging for the detection of inducible ischaemia and for the risk stratification of patients with ischaemic heart disease, and (iv) enabled the diagnostic classification of patients with transplant vasculopathy, cardiomyopathies, pulmonary hypertension, and diabetic heart disease. SENC has the potential to detect a wide range of myocardial diseases early, accurately, and without the need of contrast agent injection, possibly enabling the initiation of specific cardiac therapies during earlier disease stages. Its one-heartbeat acquisition mode during free breathing results in shorter cardiovascular magnetic resonance protocols, making its implementation in the clinical realm promising.
First published: 25 April 2019
Gesehen am 19.05.2020